An Analysis of Orange Peel (Citrus Sinensis) as the Material for Electrolystes in Bio-Batteries - Fahmi Salafa; Latiful Hayat; Anwar Ma'ruf (Jurnal Riset Rekayasa Elektro, 2020)
Efforts to reduce the use of chemicals that pollute the environment need innovations to tackle the problem. One of them is to replace the chemicals contained in the battery by utilizing the waste of orange peel. Citrus skin has citric acid (C6H8O7) which can be used as an electrolyte solution as the contents of the battery because the citric acid can produce cations and anions that conduct electricity. This research aims to make the latest innovations so that the battery used now not only depends on synthetic chemicals, determining the pH value of the orange peel is suitable to serve as electrolyte-making material in Battery, look for the current strong value as well as the maximum voltage that can be generated from unused parts of the fruit as an electrolyte in the battery, understand the principle of bio-battery work by utilizing the Orange peel as a material maker Its electrolyte, utilizing the abundant natural resources as well as possible, reduces the environmental pollution effect due to the content of the battery content made from synthetic chemicals. The research method is done by sorting the orange peel then smoothed, after it was given the addition of H2O water, the mixing is left evenly mixed, then separate the water with the orange skin mixed. After that, the water is mixed with wood charcoal and dried until the water is 50% reduced, so it is ready to be used as an electrolyte on the battery. The results showed that the orange Peel had a pH of 3.8 and had acidic properties so that it could be used as an electrolyte on batteries. The electrolyte produced by the orange Peel produces a voltage of 0.81 volts and has a strong current of 0.049 mA with a resistor load mounting of 4.7 KΩ. Battery capacity with a length of 4 cm, width of 2 cm and a height of 9 cm to produce a battery capacity that can be utilized by 4.752 mAH with a voltage of 0.8 Volt.